THE SP3OR’S POLICY EVALUATION IN SDP PERSPECTIVE: NEW DIRECTION FOR SPORTS DEVELOPMENT IN THE FUTURE - Hardiyani, Destri; Saputra, Yudha Munajat; Ma’mun, Amung (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
The purpose of this study was to determine the SP3OR’s policy in the perspective of  sport development and peace (SDP) for new directions of sports development in the future. Qualitative research was conducted, where semi-structured interview data were collected from participants, as were data from direct participant observations and organizational documents. Data analysis followed, according to triangulation. The results of this study indicate that the SP3OR’s program through its tasks or activities to the community has received a very positive response, an increase in the number of community participation in sports in West Java Province tends to increase every year. So that the SP3OR’s program is contained in the policy of Governor Regulation (Pergub) No.7 of 2018 so that the consistency of programs running in the community is maintained. Thus the SP3OR’s Program in West Java is expected to become an example for other provinces in Indonesia so that they can utilize human resources, especially youth, to build a human development index through sports activities.